2017
DOI: 10.1016/j.jpba.2017.06.054
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the phase I and phase II metabolic profile of tolvaptan by in vitro studies and liquid chromatography–mass spectrometry profiling: Relevance to doping control analysis

Abstract: Phase I and phase II biochemical reactions involved in the biotransformation pathways of tolvaptan were characterized by LC-MS-based techniques and in vitro models to identify the most appropriate marker(s) of intake. The effects of physiological and non-physiological factors on the metabolic profile of tolvaptan were also evaluated. In vitro approaches were based on the use of pooled human liver microsomes and recombinant isoforms of cytochrome P450 and uridine diphospho glucuronosyl-transferase. Sample prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…Originally banned as non-approved substances (Class 15 The goal of the present work is to extend the knowledge about the metabolic profile of SR9009, also considering the effects of gender, genetic polymorphism, and drug-drug interaction. For this purpose, following similar studies performed on other classes of substances prohibited in sport, [17][18][19] in vitro metabolism studies were performed to characterize (a) the phase I and phase II metabolic pathways; (b) the isoenzymes involved in the phase I biotransformation reactions; and (c) the potential alteration of the above caused by gender differences, genetic polymorphism, and drug-drug interaction. The non-prohibited drugs were selected from those most commonly used by the athletes (according to the information available on the doping control form) and/or reported to be inhibitors of the CYP450 system [20][21][22][23] Specifically, four antifungals (ketoconazole, miconazole, itraconazole, and fluconazole), three antidepressants (paroxetine, fluoxetine, and nefazodone), three non-steroidal anti-inflammatory drugs (NSAIDs; ibuprofen, ketoprofen, and diclofenac), two H2 receptor antagonists (ranitidine and cimetidine), and two steroidal progestins (gestodene and levonorgestrel) were considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally banned as non-approved substances (Class 15 The goal of the present work is to extend the knowledge about the metabolic profile of SR9009, also considering the effects of gender, genetic polymorphism, and drug-drug interaction. For this purpose, following similar studies performed on other classes of substances prohibited in sport, [17][18][19] in vitro metabolism studies were performed to characterize (a) the phase I and phase II metabolic pathways; (b) the isoenzymes involved in the phase I biotransformation reactions; and (c) the potential alteration of the above caused by gender differences, genetic polymorphism, and drug-drug interaction. The non-prohibited drugs were selected from those most commonly used by the athletes (according to the information available on the doping control form) and/or reported to be inhibitors of the CYP450 system [20][21][22][23] Specifically, four antifungals (ketoconazole, miconazole, itraconazole, and fluconazole), three antidepressants (paroxetine, fluoxetine, and nefazodone), three non-steroidal anti-inflammatory drugs (NSAIDs; ibuprofen, ketoprofen, and diclofenac), two H2 receptor antagonists (ranitidine and cimetidine), and two steroidal progestins (gestodene and levonorgestrel) were considered.…”
Section: Introductionmentioning
confidence: 99%
“…Product ion spectra obtained at collision energy 30 eV, molecular structure, fragmentation pathways and structural markers conditions were optimized (protein and substrate concentrations, buffer and solvent types, incubation time) considering the protocols already used in previous studies carried out in our laboratory [17][18][19]24. Different solvents (methanol, DMSO, and acetonitrile), buffers (phosphate and tris-HCl), pH values (480, and 720 minutes) were evaluated.…”
mentioning
confidence: 99%
“…Both CYP3A4 and CYP3A5 mediate the cholesterol biotransformation to 4β‐OHC . In vitro metabolism of tolvaptan was faster using human liver microsomes with CYP3A5*1/*1 than with *1/*3 or *3/*3 . Our data indicate that tolvaptan is metabolized by CYP3A5 rather than CYP3A4 in human beings.…”
Section: Discussionmentioning
confidence: 77%
“…9 Tolvaptan and its metabolites are predominantly eliminated by hepatic CYP3A4/5 in human beings. 7 In addition, tolvaptan is a substrate of and a weak inhibitor of P-glycoprotein, ABCB1 transporter, which is involved in the intestinal secretion and multidrug resistance. 10 CYP3A activity varies among human individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Modern analytical instruments as routinely applied in doping controls provide the necessary sensitivity and selectivity to unequivocally determine classes of prohibited substances including diuretics and other masking agents, stimulants and narcotics readily meeting WADA's MRPL. Consequently, method optimization or new test assay developments are scarce concerning these doping agents; however, research concerning metabolism or factors potentially affecting urinary concentrations of these substances have been investigated as for example concerning the vasopressin receptor antagonist tolvaptan . In a comprehensive in vitro metabolism study, more than 20 phase I metabolites of the diuretic agent were identified, with hydroxylated and carboxylated species either in unconjugated or glucuronidated form were suggested as ideal candidates for sports drug testing methods.…”
Section: Diuretics and Other Masking Agents Stimulants Narcotics Amentioning
confidence: 99%